Drinking Orange Juice or Eating Orange Fruit: Which is Better for Glycemic Control? (AYUSHDHARA, 2024)
The consumption of 100% fruit juice has been a subject of controversy due to abundance of free sugars leading to inconsistent dietary guidelines. This study aimed to verify the hypothesis if eating whole fruit scores better than drinking fruit juices in terms of glycemic control. 15 type-2 diabetic patients volunteered from author’s online Diabetes Reversal Program to participate in the observational study. The relative effect of consumption of 300-ml orange FJ and 300-gram whole orange fruit on glycemic control was compared to verify the hypothesis. The findings of the study suggested that the consumption of oranges (whether juiced or eaten whole) is safe and well tolerable for diabetics and does not substantially raise the blood glucose levels in the average diabetic, however, individualized dietary modification would be the optimal practice to achieve desired health outcomes.